New aesthetic in-house 3D-printed brackets: proof of concept and fundamental mechanical properties - Spyridon N. Papageorgiou; Georgios Polychronis; Nearchos Panayi; Spiros Zinelis; Theodore Eliades (SpringerOpen, 2022)
Abstract Objectives Three-dimensional (3D) printing technology is an emerging manufacturing process for many orthodontic appliances, and the aim of this study was to evaluate the mechanical properties of resin-based materials as alternatives for the in-house preparation of orthodontic brackets. Material and Methods Two types of 3D printed resins used for temporary (T) and permanent (P) crown fabrication were included in this study. Ten blocks from each resin were manufactured by a 3D printer and, after embedding them in acrylic resin, the samples were subjected to metallographic grinding and polishing, followed by instrumented indentation testing (IIT). Martens hardness (HM), indentation modulus (E IT), and elastic index (η IT) were determined with a Vickers indenter recording force-indentation depth curves from each specimen. After calculating descriptive statistics, differences between material types were investigated with Wilcoxon rank sum test accounting for clustering of measurements within specimens at alpha = 5%. Results No statistically significant differences in the mechanical properties of the two tested materials were seen: HM: median 279 N/mm2 (interquartile range [IQR] 275-287 N/mm2) for T and median 279 N/mm2 (IQR 270-285 N/mm2) for P (P value = 0.63); E IT: median 5548 MPa (IQR 5425-5834 MPa) for T and median 5644 (IQR 5420-5850 MPa) for P (P value = 0.84); η IT: median 47.1% (46.0-47.7%) for T and median 46.0% (IQR 45.4-47.8%) for P (P value = 0.24). Conclusions Under the limitations of this study, it may be concluded that the mechanical properties of the two 3D printed resins tested are equal, and thus, no differences in their clinical performance are expected.